Methodological Bases for Planning the Economic Safety of an Enterprise - DANILOVA, Elvira I.; MARCHENKO, Valentyna M. (Journal of Advanced Research in Law and Economics, 2019)
On the basis of the analysis of the existing scientific approaches to planning of economic safety of an enterprise, the methodological provisions of planning the economic safety of the enterprise were developed in the part concerning the formation of specific principles of planning the economic safety; identification of component, functional and systemic hazards; aggregation of stages of planning of economic safety of an enterprise. The generalization of practical approaches to the planning of economic safety allowed us to form its basic postulates, which are: submission of current plans to the strategic plan of economic safety; submission of the rules of economic security to the plans of the enterprise; complexity and interconnectedness of plans of economic, informational, authority, ecological safety. The scientific approaches to the interpretation of the economic essence and the logical sequence of actions in the part of the assessment and analysis of threats, hazards and risks are systematized. The criteria for identifying threats, hazards and risks are theoretically defined. It is analytically proven that at any time in the company there is a set of threats, hazards and risks of different nature of origin, therefore the methodical planning tools should be based on a combination of methods of evaluation and prevention of all types of present threats, the hazards of past threats and current risks of past threats and future risks of the present threats Taking into account the totality of objects of threats, dangers and risks in the activity of enterprises, the stages of planning the economic safety of an enterprise are proposed, implementation of which allows to identify, assess and develop a set of measures for their avoidance or reduction of losses from their occurrence.